1989
DOI: 10.1007/bf00239447
|View full text |Cite
|
Sign up to set email alerts
|

Intramembrane particles and filipin labelling on the membranes of autophagic vacuoles and lysosomes in mouse liver

Abstract: Morphologically detectable protein (intramembrane particles) and cholesterol (filipin labelling) in the membranes of autophagic vacuoles and lysosomes were studied in mouse hepatocytes using thin-section and freeze-fracture electron microscopy. Both isolated autophagic vacuoles and lysosomes, and intact tissue blocks were used due to the facts (i) that lysosomes are difficult to recognize in freeze-fracture replicas of intact hepatocytes, and (i) that filipin penetration into the tissue blocks is unsatisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…We observed that the same applies to membrane cholesterol. Phagophores have no detectable cholesterol, but the cholesterol content increases during the maturation to early and late autophagic vacuoles 35 (Fig. 2).…”
Section: Fusion Events With Endosomes and Lysosomesmentioning
confidence: 95%
See 1 more Smart Citation
“…We observed that the same applies to membrane cholesterol. Phagophores have no detectable cholesterol, but the cholesterol content increases during the maturation to early and late autophagic vacuoles 35 (Fig. 2).…”
Section: Fusion Events With Endosomes and Lysosomesmentioning
confidence: 95%
“…Based on morphological, cytochemical and immunoelectron microscopy data, autophagosomes are proposed to originate from the membranes of the endoplasmic reticulum. 11 However, the structural and biochemical characteristics of these membranes are different from the endoplasmic reticulum, [35][36][37][38] and thus the phagophores or isolation membranes should probably be regarded as distinct organelles.…”
Section: Autophagy Genesmentioning
confidence: 99%
“…In quickly frozen and fractured cells the fracture runs preferentially along the hydrophobic plane of the membranes, allowing characterization of the limiting membranes of the different types of autophagic vacuoles and visualization of their limited protein intramembrane particles (IMPs, or integral membrane proteins). Several studies have been performed using this technique on yeast, 53 as well as on mammalian cells or tissue, first on mouse exocrine pancreas, 54 then on mouse and rat liver, 55,56 mouse seminal vesicle epithelium 24,51 or cancer cell lines (e.g., breast cancer MDA-MB-231) 57 to investigate the various phases of autophagosome maturation, and to reveal useful details about the origin and evolution of their limiting membranes. 2,8,[58][59][60] The phagophore and the limiting membranes of autophagosomes contain few, or no detectable, IMPs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3C). 8,24,[53][54][55][56]61,62 Autolysosomes are generally delimited by a single membrane because, in addition to the engulfed material, the inner membrane is degraded by the lytic enzymes. Similarly, the limiting membrane of autophagic bodies in yeast and plants is also quickly broken down under normal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2,9 Furthermore, freeze-fracture studies have shown that phagophores and autophagosomes differ from other membranebounded organelles in having delimiting membranes with exceptionally few of the intramembrane particles that correspond to transmembrane proteins. [10][11][12][13] However, although autophagosomes and phagophores may be deficient with respect to transmembrane proteins, recent studies have identified several proteins that appear to be peripherally associated with the membranes of these organelles. In mouse embryonic stem cells, the mammalian homologues of Atg5 and Atg8, two of the proteins required for autophagy in yeast, were found to bind to sequestering membranes that apparently correspond to phagophores.…”
Section: Introductionmentioning
confidence: 99%